Promoting the Wellness of Older Adults through Integrated Health-Promoting Programs and Supportive Peers: A Quasi-Experimental Study in Semi-Urban Communities of Northeastern Thailand - Tassanee Silawan; Arpaporn Powwattana; Phurithat Ponsen; Nuttawat Ninkarnjanakun (SAGE Publishing, 2024)
Introduction/Objectives: Thailand has approached an aged society in which the proportion of older adults rose from 5% in 1995 to 20.7% in 2022 and is projected to increase to 27.2% in 2030. Older adults face health risks and challenges, requiring supportive care. This research aimed to promote the wellness of older adults through Integrated Health-Promoting Programs and Supportive Peers (IHPP-SP) in semi-urban communities. Methods: A one-group pretest-posttest quasi-experimental study was conducted among 229 older adults from 22 communities. The interventions covered analyzing community situations and determinants, designing and developing IHPP-SP, enhancing the capabilities of supportive peers, and establishing a support system. Mean and proportion differences were analyzed using the paired t -test and McNemar test. Results: After implementing IHPP-SP, the mean score significantly increased for happiness ( P  = .004), Activities of Daily Living: ADLs ( P  = .034), and family support ( P  < .001), but did not differ regarding depression ( P  = .413). The proportion of healthy behaviors significantly increased for tobacco use ( P  = .035), dietary intake ( P  = .018), and physical activity ( P  < .001), but not for alcohol consumption ( P  = .377). Conclusions: The IHPP-SP provided potential benefits to promote the wellness of older adults.